Dr Adesina 1st speech at Agriserve - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Dr. Akinwumi Adesina giving his 1st speech at the Agriserve Building at IITA 50th anniversary in Ibadan on 24 July 2017.